2022
DOI: 10.1002/cam4.5155
|View full text |Cite
|
Sign up to set email alerts
|

Pylorus‐preserving versus Pylorus‐resecting: Impact on dynamic changes of nutrition and body composition in pancreatic cancer patients before and after pancreatoduodenectomy

Abstract: Objectives To investigate if different methods of pancreatoduodenectomy (with or without pyloric preservation) would have different impacts on postoperative nutrition and body composition changes among pancreatic cancer patients. Methods Demographic and clinicopathological data, perioperative data were collected, body composition (e.g. skeletal muscle cross‐sectional area [CSA], visceral fat area [VFA]) were evaluated with abdominal CT before and after surgery. Sarcopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A multi-center study conducted in the USA showed that sarcopenia is more prevalent in patients with inflammatory bowel disease undergoing surgery, while the clinical nutrition markers including the body mass index and albumin were similar in the population (33). It is also reported that patients who underwent different methods of pancreatoduodenectomy may also have different changes in skeletal muscle cross-sectional area and visceral fat area, and the incidence of sarcopenia in both surgical procedures continued to increase (34). Many studies paid more attention to the role of nutrition in sarcopenia and surgery (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…A multi-center study conducted in the USA showed that sarcopenia is more prevalent in patients with inflammatory bowel disease undergoing surgery, while the clinical nutrition markers including the body mass index and albumin were similar in the population (33). It is also reported that patients who underwent different methods of pancreatoduodenectomy may also have different changes in skeletal muscle cross-sectional area and visceral fat area, and the incidence of sarcopenia in both surgical procedures continued to increase (34). Many studies paid more attention to the role of nutrition in sarcopenia and surgery (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%